Leg stiffness in female soccer players: Intersession reliability and the fatiguing effects of soccer-specific exercise - De Ste Croix, M. B. A.; Hughes, J. D.; Lloyd, R. S.; Oliver, J. L; Read, P. J. (The Journal of Strength and Conditioning Research, 2017)
Low levels of leg stiffness and reduced leg stiffness when fatigue is present compromise physical performance and increase injury risk. The purpose of this study was to (a) determine the reliability of leg stiffness measures obtained from contact mat data and (b) explore age-related differences in leg stiffness after exposure to a soccer-specific fatigue protocol in young female soccer players. Thirty-seven uninjured female youth soccer players divided into 3 subgroups based on chronological age (under 13 [U13], under 15 [U15], and under 17 [U17] year-olds) volunteered to participate in the study. After baseline data collection, during which relative leg stiffness, contact time, and flight time were collected, participants completed an age-appropriate soccer-specific fatigue protocol (SAFT90). Upon completion of the fatigue protocol, subjects were immediately retested. Intersession reliability was acceptable and could be considered capable of detecting worthwhile changes in performance. Results showed that leg stiffness decreased in the U13 year-olds, was maintained in the U15 age group, and increased in the U17 players. Contact times and flight times did not change in the U13 and U15 year-olds, but significantly decreased and increased, respectively, in the U17 age group. The data suggest that age-related changes in the neuromuscular control of leg stiffness are present in youth female soccer players. Practitioners should be aware of these discrepancies in neuromuscular responses to soccer-specific fatigue, and should tailor training programs to meet the needs of individuals, which may subsequently enhance performance and reduce injury risk.